A qualitative exploration of stress in a criminal investigations section - Padilla, Kathleen E. (Replicating & reproducing policing research, 2024)
Traditional literature on stress in policing focuses on patrol officers and generalizes findings to other sections and ranks within the department. This fails to take into consideration that different sections may experience and manage stress in various ways. Following Dabney and colleagues (2013) examination of homicide investigators, the current study employs deductive coding to examine interviews from 21 investigators from financial, property, domestic violence, persons, and child crimes in the Criminal Investigations Section of a mid-sized Southwestern, United States police department. Findings were able to both replicate and expand upon Dabney and colleagues (2013) results, suggesting that even in a department that varies demographically and operationally from the original department, these investigators were exposed to and afflicted by many of the same stressors. While some of these stressors were similar to their patrol officer counterparts, investigators were further impacted by sources of stress that are unique to their specific role in the police organization (e.g., heavy caseloads, prolonged exposure to trauma, additional involvement with other criminal justice actors). Research and practical implications for departments - both international and domestic - in managing investigator stress are discussed.